1992
DOI: 10.1080/03079459208418817
|View full text |Cite
|
Sign up to set email alerts
|

Electrocardiogram of the African grey (psittacus erithacus) and Amazon (Amazonaspp.) parrot

Abstract: SUMMARYElectrocardiographic reference values and configurations were established in apparently healthy African grey (Psittacus erithacus; n=45) and Amazon (Amazona spp.; n = 37) parrots, using standard limb leads. In 31 of the African grey parrots and 32 of the Amazon parrots electrocardiograms were made during isoflurane-anaesthesia. Significant differences between anaesthetized and unanaesthetized birds were found only for the median heart rate and QTinterval (P<0.05). Significant differences between the two… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
34
1
6

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 51 publications
(49 citation statements)
references
References 7 publications
8
34
1
6
Order By: Relevance
“…In our study, the ST segment was almost identifiable in all tracings, and ST slurring was found in only one tracing. In agreement with previous ECG studies on other bird species [14,16,33,35] , the ST segment mainly appeared elevated over baseline.…”
Section: Tablo 2 Dişi Ve Erkek Sülünlerde P Qrs Ve T Dalgalarına Aisupporting
confidence: 80%
See 4 more Smart Citations
“…In our study, the ST segment was almost identifiable in all tracings, and ST slurring was found in only one tracing. In agreement with previous ECG studies on other bird species [14,16,33,35] , the ST segment mainly appeared elevated over baseline.…”
Section: Tablo 2 Dişi Ve Erkek Sülünlerde P Qrs Ve T Dalgalarına Aisupporting
confidence: 80%
“…A normal sinus rhythm was assessed in all pheasants and no remarkable arrhythmia was found in our study in contrast with other studies on anesthetized birds [14,15] . The mean heart rates of male and female pheasants were similar and were 194 bpm and 236 bpm, respectively.…”
Section: Tablo 2 Dişi Ve Erkek Sülünlerde P Qrs Ve T Dalgalarına Aicontrasting
confidence: 54%
See 3 more Smart Citations